A change in coral extension rates and stable isotopes after El Niño-induced coral bleaching and regional stress events. - Hetzinger, S.; Pfeiffer, M.; Dullo, W.; Zinke, Jens; Garbe-Schönberg, D. (Nature Publishing Group, 2016)
Coral reefs are biologically diverse ecosystems threatened with effective collapse under rapid climate change, in particular by recent increases in ocean temperatures. Coral bleaching has occurred during major El Niño warming events, at times leading to the die-off of entire coral reefs. Here we present records of stable isotopic composition, Sr/Ca ratios and extension rate (1940-2004) in coral aragonite from a northern Venezuelan site, where reefs were strongly impacted by bleaching following the 1997-98 El Niño. We assess the impact of past warming events on coral extension rates and geochemical proxies. A marked decrease in coral (Pseudodiploria strigosa) extension rates coincides with a baseline shift to more negative values in oxygen and carbon isotopic composition after 1997-98, while a neighboring coral (Siderastrea siderea) recovered to pre-bleaching extension rates simultaneously. However, other stressors, besides high temperature, might also have influenced coral physiology and geochemistry. Coastal Venezuelan reefs were exposed to a series of extreme environmental fluctuations since the mid-1990s, i.e. upwelling, extreme rainfall and sediment input from landslides. This work provides important new data on the potential impacts of multiple regional stress events on coral isotopic compositions and raises questions about the long-term influence on coral-based paleoclimate reconstructions.